DARI KECEPATAN KE KEAMANAN: EVOLUSI PINJAMAN ONLINE DAN PERLINDUNGAN KONSUMEN DI INDONESIA - Rengga Yudha Santoso; Ajeng Ratri Kirana Dewi (CV. Adiba Aisha Amira, 2025)
The rapid development of financial technology (fintech) in Indonesia has significantly transformed the landscape of digital financing, particularly through online lending (peer-to-peer lending). These platforms provide quick and convenient access to funds, especially for underbanked segments, but also create new risks such as high interest rates, unethical collection practices, and misuse of personal data. This study aims to analyze the evolution of online lending services from a focus on speed toward security, and to examine the effectiveness of regulatory frameworks and consumer protection in Indonesia. A qualitative literature review method was employed, drawing from Scopus-indexed journals, Financial Services Authority (OJK) regulations, Law No. 27/2022 on Personal Data Protection, and international policy reports. The findings reveal that OJK Regulation No. 10/POJK.05/2022 has strengthened governance standards, interest rate caps, and consumer protection mechanisms; however, challenges remain in supervising illegal platforms, ensuring cost transparency, and improving digital financial literacy. In conclusion, the evolution of Indonesia’s online lending sector reflects a shift from speed-driven innovation to security and sustainability, where effective consumer protection relies on robust regulation, inter-agency coordination, and public awareness. Policy recommendations include enhancing technology-based supervision (regtech), expanding financial literacy programs, and conducting impact evaluations of existing regulations on consumer welfare.